Take your last breath - Child, Lauren (Child, Lauren. Ruby Redfort (Series), 2018)
Thirteen-year-old Ruby, a secret agent and code cracker, investigates the strange marine disturbances happening around the world while also trying to find her parents who are missing at sea.